2022
DOI: 10.1117/1.nph.9.4.041411
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning in fNIRS: a review

Abstract: Significance: Optical neuroimaging has become a well-established clinical and research tool to monitor cortical activations in the human brain. It is notable that outcomes of functional nearinfrared spectroscopy (fNIRS) studies depend heavily on the data processing pipeline and classification model employed. Recently, deep learning (DL) methodologies have demonstrated fast and accurate performances in data processing and classification tasks across many biomedical fields.Aim: We aim to review the emerging DL a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 106 publications
0
35
0
Order By: Relevance
“…For this compile stage, we set the learning rate, batch size, and the number of epochs as HPs for auto-tuning. Unlike most works that chose typical HPs like the number of neurons, dropout rate, learning rates, and the number of epochs for auto-tuning [29], [44], [45], we also included activation functions, batch size, and most importantly, network structures as our auto-tuned HPs, which were as much we can auto-tune as possible. The 2D and 3D CNN networks were constructed similarly to the MLP network.…”
Section: Model Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this compile stage, we set the learning rate, batch size, and the number of epochs as HPs for auto-tuning. Unlike most works that chose typical HPs like the number of neurons, dropout rate, learning rates, and the number of epochs for auto-tuning [29], [44], [45], we also included activation functions, batch size, and most importantly, network structures as our auto-tuned HPs, which were as much we can auto-tune as possible. The 2D and 3D CNN networks were constructed similarly to the MLP network.…”
Section: Model Constructionmentioning
confidence: 99%
“…Our research found three main challenges we wanted to solve using fNIRS signals and deep learning methods to classify MCI vs. CN. Firstly, while many works used fNIRS signals with deep learning methods for other diagnoses (like detecting the pain intensity, epileptic seizure, and autism spectrum disorder), cortical analysis, and brain-computer interface and showed accurate classification results [27]- [29], only a few works utilized deep learning methods to detect MCI vs. CN [26], [30]. Secondly, deep learning methods require a large amount of data to prevent overfitting, yet the existing studies in our area mostly had small datasets of less than 50 participants [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, performing SSH and TTL on LI 11 is a good choice for ARRMs neuroimaging research. In recent years, functional near-infrared spectroscopy (fNIRS) has emerged as a well-established imaging tool for neuroscience research (Eastmond et al, 2022). It has a high temporal resolution (Tak and Ye, 2014) and the capacity for monitoring in real clinical settings (Dybvik and Steinert, 2021;Gossé et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To our best knowledge, this is the first review that covers machine learning studies focusing on biomarker research using fNIRS. There is a recent review focusing on deep learning (Eastmond et al, 2022), however, as we stated above we also discussed the regions and potential biomarkers used as a feature that provides high diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%